Efeito inibitório in vitro do composto farnesol frente ao biofilme de Burkholderia pseudomallei - Correia, Giovanna Riello Barbosa (2015)
The intrinsic antimicrobial resistance of Burkholderia pseudomallei is a serious challenge to the treatment of melioidosis. Many studies have searched for adjuvants that increase susceptibility bacteria to antimicrobials. In this context, the antimicrobial activity of farnesol against B. pseudomallei in planktonic growth has been reported. Thus, the aim of this study was to analyze the in vitro activity of farnesol alone against Burkholderia pseudomallei biofilms, as well as its combination with the antibacterials amoxicillin, doxycycline, ceftazidime and sulfamethoxazole-trimethoprim. Susceptibility was assessed by the broth microdilution test and cell viability was read with the oxidation-reduction indicator dye resazurin. The interaction between farnesol and antibacterial drugs against B. pseudomallei biofilms was evaluated through the calculation of the fractional inhibitory concentration index. The minimum biofilm erradication concentration (MBEC) for farnesol was 75 to 2400 mM. In addition, farnesol significantly reduced the MBEC values for ceftazidime,amoxicillin, doxycycline and sulfamethoxazole-trimethoprim by 256, 16, 4 and 4 times respectively (P<0.05). Optical, confocal and electronic microscopic analyses of farnesol treated B. pseudomallei biofilms demonstrated that this compound damages biofilm matrix,facilitating antimicrobial penetration in the biofilm structure. This study demonstrated the effectiveness of farnesol against B. pseudomallei biofilms and its potentiating effect on the activity of antibacterial drugs, in particular ceftazidime, amoxicillin, doxycycline and sulfamethoxazole-trimethoprim.